2014
DOI: 10.1038/ejcn.2014.206
|View full text |Cite
|
Sign up to set email alerts
|

Daily iodine intake and the impact of salt reduction on iodine prophylaxis in the Italian population

Abstract: Our study suggests that the recommended quantities of salt, if iodized at 30 mg/kg, are sufficient to achieve the adequate daily iodine intake both in adults and children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 22 publications
4
19
2
Order By: Relevance
“…From one hand our results suggest that there are improvements to be made for a comprehensive take up of the policy nationally. On the other hand it confirms that both iodization and salt reduction policies are fully compatible, as agreed in a WHO Consensus Statement [31] and more recently confirmed in case studies in Italy [52] and China [53] where a moderate salt reduction in unlikely to compromise iodine status. Our data provides a useful baseline against which to monitor the impact of future initiatives.…”
Section: Discussionsupporting
confidence: 72%
“…From one hand our results suggest that there are improvements to be made for a comprehensive take up of the policy nationally. On the other hand it confirms that both iodization and salt reduction policies are fully compatible, as agreed in a WHO Consensus Statement [31] and more recently confirmed in case studies in Italy [52] and China [53] where a moderate salt reduction in unlikely to compromise iodine status. Our data provides a useful baseline against which to monitor the impact of future initiatives.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, regional differences in iodine concentration should not have influenced our results since a study reported no differences among the centers participating in the study (34). …”
Section: Discussionmentioning
confidence: 94%
“…The average daily intake of iodine in the general population is less than that indicated by WHO, at the European level, where iodine deficiency affects mainly the child population [43], and all over the Italian territory (85–88 µg/day vs. 150 µg/day) [44]. …”
Section: Micronutrientsmentioning
confidence: 99%